ENT 600 : Blueprint : Smart money box / Nurul Atisyah Amran, Nur Fatini Nadziri @Ismail and Mohammad Amir Suhairi Zuhairy - Amran, Nurul Atisyah; Nadziri @ Ismail, Nur Fatini; Suhairi Zuhairy, Mohammad Amir (2018)
The team, which is an AFA Group are developing a Smart Money Box or SMO for short. This device is actually an innovation of an old version piggy bank that had existed nowadays. The significance function of SMO is that it can split money according to their value of note or coin. It is also designed with several complex machinery such as a scanner and quantity display. The target market for this product is for parents that have children between 7 to 17 years old because this product is very suitable for children or others who have hard time to manage their money. The Smart Money Box has a huge chance in Malaysia market since it only need to compete with the conventional piggy bank that already available in the market. Other than our company, there is no company or inventors that commercialize this kind of product. The cost to produces the product are also low which is below RM200, so it can sell in the market in an affordable range.